Lifetime Memories of Inflation: Evidence from Surveys and the Lab - Isabelle Salle; Yuriy Gorodnichenko; Olivier Coibion (Institute of Labor Economics (IZA), 2023)
We study how individuals' memories of inflation shape their expectations about future inflation using both surveys and laboratory experiments. Recalling having lived through prior disinflations has pronounced effects on how long-lived people expect the current inflation episode to last. Information treatments in which we show people prior disinflationary experiences similarly strongly reduce inflation expectations of individuals on average and are often recalled as inflation memories months later. We also show that when people try to forecast inflation in the lab, the inflation dynamics in the game can affect their beliefs much like the inflation experienced in real life. Methodologically, we compare and contrast surveys and lab experiments and discuss the pros and cons of each method, emphasizing the general consistency across the two methodologies.
Keywords: E3; E4; E5; 330; inflation experience; experiments; surveys; randomized control trial